Patterns of Exclusion in the Education System: A Case Study of Musahar Children in Bihar - Gupta, Priti (JOURNAL OF INDIAN EDUCATION, 2026)
Musahar children come from extremely marginalised socio-economic backgrounds, shaped by chronic poverty, caste-based exclusion, and limited access to education. Their cultural context — — rooted in generations of landlessness and manual labour — deeply influences their daily struggles, including the inability to access basic necessities such as food, clothing, and school materials. These challenges severely affect their participation in school. At the Musahar Toil School, most teachers belong to more privileged caste and class backgrounds. As a result, they often lack the sensitivity or awareness to understand the specific needs and barriers faced by Musahar children. This disconnects leads to exclusion in three significant ways. First, teachers exhibit indifference toward the children’s irregular attendance, failing to explore the socio-economic reasons behind it. Second, they rely on conventional teaching methods that are not suited to first-generation learners. Third, the use of mixed or inconsistent teaching approaches often ignores the children’s cultural context, making learning disengaging and inaccessible. These factors collectively contribute to a growing disinterest in education among Musahar children, resulting in high dropout rates. This paper uses a case study approach to examine how teacher behaviour and classroom practices shape the educational experiences of Musahar children and perpetuate patterns of exclusion.